Development of 2.4 GHz/3.5 GHz Bowtie Slot Antenna for 5G Communication System - Ting Sing Wee, Richard; Zainal Abidin, Intan Sorfina; Abd Aziz, Azniza (International Journal of Integrated Engineering, 2025)
Driven by the rapid growth and advancements in 5G communication, this research presents the the design, development, and optimization of of dual-band bowtie slot antenna integrated with asymmetrical coplanar waveguide (ACPW) and defected ground structure (DGS). Several combinations and different shape of DGS, such as rectangular and circular slots were studied and compared in this research work. Operating at the crucial Wi-Fi frequency (2.4 GHz) and 5G frequency (3.5 GHz), the antenna’s performance, particularly the reflection coefficient, was significantly improved by the inclusion of the DGS. A parametric study confirmed the DGS’s positive impact on the simulated impedance matching, reflection coefficient (reaching almost -70 dB in all design with DGS) and bandwidth. The best resuts were given by the bowtie slot antenna integrated with rectangular and circular slots, the reflection coefficient is -70.1 dB (2.4 GHz) and -59.5 dB (3.5 GHz). The -10 dB bandwidths are 602 MHz (2.4 GHz) with fractional bandwidth around 25% and 848 MHz (3.5 GHz) with fractional bandwidth around 24.2%. It was found that the excellent reflection coefficient performance is due to the disruption of surface current distribution caused by the defected structure on the ground plane. The surface current was forced to flow surrounding the DGS, causing it to peak along the DGS edges. Placement of the DGS is also important as it was found that positioning it under the feedline helps to minimize the antenna’s mutual coupling.